Seismic catalogs of the 2020-2021 seismic swarm at the Bransfield Strait, Antarctica - Cesca, Simone; Sugan, Monica; Rudzinski, Łukasz; Vajedian, Sanaz; Niemz, Peter; Plank, Simon; Petersen, Gesa Maria; Deng, Zhiguo; Rivalta, Eleonora; Vuan, Alessandro; Plasencia Linares, Milton Percy; Heimann, Sebastian; et al. (Zenodo, 2022)
Three seismic catalogs are available: 1. Single station catalog for station JUBA based on the Lassie software 2. Moment tensor inversion catalog with moment tensor classification 2. Template matching catalog